Aqueous battery based on azine derivative and preparation method thereof
By using PDAP as the negative electrode material in the water system, and adding 1,4-epoxy six-ring and second-based sub-macaron to the electrolyte, the highly dissolved and short cycle life of the azine material in the water cell battery is solved. The problem has achieved the effect of high energy density and long cycle life.
Patent Information
- Application Number
- CN202411232181.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-21
AI Technical Summary
Existing water-based batteries have problems with low energy density and short cycle life in the application of zine-based materials, and the solubility of zine-based materials is high, which affects the cycle stability of the battery.
PDAP with a 2,3-diosamophenzide (DAP) (DAP) is used as an organic negative electrode material, and the 1,4-epoxy six-ring and the second metropolitaniah is added to the electrolyte to weaken the solubility of organic materials. , Broaden the electrochemical window.
It achieves long cycle life and high output voltage of aqueous batteries, solves the problems of low energy density and short cycle life, and improves battery stability.
Smart Images

Figure CN119340506A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aqueous batteries, and in particular relates to an aqueous battery based on azine derivatives and a preparation method thereof. Background Art
[0002] In order to cope with the depletion of fossil fuels and environmental degradation, and the uneven distribution of new energy sources such as wind energy and tidal energy in time and space, the development of safe and efficient energy storage technology has become a research hotspot today. Among them, lead-acid batteries are widely used due to their low price and safety, but their disadvantages are short life, low energy density, and high operation and maintenance costs. Although lithium-ion batteries (LIBs) have high energy density, they are potentially flammable and explosive. In order to meet more and more energy storage requirements, aqueous organic batteries (ARBs) are considered to be the most promising battery technology. ARBs use organic materials as the positive or negative electrode of the battery. Due to the diversity of their structure, adjustability, and the fact that organic electrode materials are not restricted by geographical resources, more and more organic materials (such as carbonyl compounds, imine compounds, conductive polymers, COFs materials, MOFs materials, etc.) have been developed and applied to ARBs.
[0003] Among them, azine materials (such as phenazine 298mAh / g) have the characteristics of high specific capacity and high stability, and are considered to be promising electrode materials for use in aqueous battery systems. However, phenazine is not conductive. Therefore, when preparing electrode sheets, more conductive agents (ketjen black, carbon nanotubes, etc.) need to be added, so that the proportion of active substances is generally less than 60%, and the mass loading is mostly 1-3mg / cm 2 , which makes the overall density of the battery low. An effective way to enhance the electrochemical performance of organic materials is to improve the conductivity of electrode materials by adjusting the molecular functional groups. Therefore, different derivatives of oxazine materials such as diaminophenazine, dihydroxyphenazine and other materials have been developed and applied to aqueous battery systems. However, these functional groups (-NH2, -OH) are hydrophilic groups. Therefore, although they can increase the electronic conductivity of oxazine materials, they are more easily dissolved in the electrolyte, resulting in poor cycle stability.
[0004] 2,3-Diaminophenazine (DAP) is a type of derivative azine material. The introduction of amino group makes the redox potential of DAP lower by 0.2V than that of phenazine (PZ), and at the same time makes its discharge platform reach 1.2V. However, the solubility of DAP limits its application in aqueous batteries. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide an aqueous battery based on azine derivatives.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0009] (iv) consisting of a positive electrode, a negative electrode, a separator and an electrolyte;
[0010] (v) the negative electrode comprises an oxazine derivative having a structural formula as shown in formula (I);
[0011]
[0012] In the formula, n represents the degree of polymerization;
[0013] X is selected from NH2, OH, NH3 + CH3COO - One of;
[0014] The electrolyte is a KOH electrolyte modified by adding 1,4-dioxane and dimethyl sulfoxide.
[0015] As a preferred embodiment of the aqueous battery based on azine derivatives of the present invention, the material of the positive electrode includes one of a nickel-based compound, a Prussian blue analogue or a polyanion compound.
[0016] As a preferred embodiment of the aqueous battery based on azine derivatives of the present invention, the material of the diaphragm includes one or more of polyethylene, polypropylene diaphragm and PBI diaphragm.
[0017] As a preferred embodiment of the aqueous battery based on oxazine derivatives of the present invention, the negative electrode further comprises Ketjen black and polytetrafluoroethylene, wherein the mass ratio of the oxazine derivatives to Ketjen black and polytetrafluoroethylene is 3 to 6:6 to 3:1.
[0018] As a preferred embodiment of the aqueous battery based on azine derivatives of the present invention, the mass ratio of 1,4-dioxane, dimethyl sulfoxide and KOH in the KOH electrolyte is 1:1:5-7.
[0019] Another object of the present invention is to provide an aqueous battery based on azine derivatives.
[0020] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0021] The CR2032 button battery is assembled with a diaphragm and a positive electrode material, using a oxazine derivative as the active material of the negative electrode and a modified KOH electrolyte as the electrolyte.
[0022] As a preferred embodiment of the method for preparing an aqueous battery based on azine derivatives of the present invention, the method for synthesizing the azine derivatives having the structural formula (I) comprises:
[0023] o-phenylenediamine is dissolved in acetic acid to form solution A;
[0024] Ammonium persulfate is dissolved in deionized water to form solution B;
[0025] Solution B is slowly added dropwise to solution A, and the mixture is heated under reflux for reaction. After the reaction is completed, the product is post-treated to obtain an oxazine derivative.
[0026] As a preferred embodiment of the method for preparing the aqueous battery based on azine derivatives of the present invention, the molar ratio of o-phenylenediamine to ammonium persulfate is 1:2-4.
[0027] As a preferred embodiment of the method for preparing aqueous batteries based on azine derivatives of the present invention, the reaction temperature of the heating reflux is 90 to 110° C., and the reaction time is 70 to 74 hours.
[0028] As a preferred embodiment of the method for preparing an aqueous battery based on azine derivatives of the present invention, the method for preparing the negative electrode comprises:
[0029] A oxazine derivative having a structural formula as shown in formula (I), Ketjen black, and polytetrafluoroethylene are mixed and then isopropyl alcohol is added. After grinding, the obtained material is vacuum dried, and the obtained material is kneaded into a clay-like state and then pressed into a thin sheet, which is pressed onto nickel foam to obtain a negative electrode.
[0030] Beneficial effects of the present invention:
[0031] The present invention uses a diaminophenazine polymer PDAP as an active substance of an organic negative electrode material, and simultaneously adds 1,4-dioxane and dimethyl sulfoxide into the electrolyte to modify the KOH electrolyte, thereby synergistically reducing the solubility of the organic material, which not only broadens the electrochemical window of the water electrolyte, but also has a higher cycle life.
[0032] The aqueous battery produced by the present invention has the advantages of long cycle life and high output voltage, and the raw materials are widely available and inexpensive. It can effectively solve the problems of low energy density and short cycle life of existing aqueous batteries, and help promote the application of aqueous batteries in the field of large-scale energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0034] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the PDAP prepared in Example 1 of the present invention.
[0035] Figure 2 This is a cyclic voltammetry curve of the PDAP prepared in Example 1 of the present invention at 5 mV / s in a three-electrode system.
[0036] Figure 3 This is a cycle stability test chart of the aqueous battery prepared in Example 1 of the present invention after 120 cycles at 0.12 A / g.
[0037] Figure 4 This is a test chart of the cycle stability of the aqueous battery prepared in Comparative Example 1 of the present invention after 120 cycles at 0.12 A / g.
[0038] Figure 5 Cyclic stability test diagram of the aqueous battery prepared in comparative example 2 of the present invention at 0.12 A / g for 120 cycles DETAILED DESCRIPTION
[0039] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0040] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0041] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0042] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.
[0043] The electrochemical performance test of the aqueous battery in the present invention refers to:
[0044] The cycle performance of aqueous batteries was tested using a new battery tester. After the battery was assembled, it was left for 12 hours before the charge and discharge test. The battery was charged first and then discharged. The voltage range was 1.5 to 0.5V, and the current density was 0.1A / g. The current size was set according to the mass of the negative electrode active material. The specific capacity of the aqueous battery was calculated based on the mass of the active material in the negative electrode.
[0045] Example 1
[0046] This embodiment provides a method for preparing an aqueous battery based on azine derivative (PDAP), specifically:
[0047] 1) Synthesize oxazine derivative PDAP according to reaction formula (II):
[0048]
[0049] 30 mmol o-phenylenediamine (o-PDA) was dissolved in 60 ml of acetic acid at 40°C to form solution A;
[0050] 90 mmol of ammonium persulfate (APS) was dissolved in 40 ml of deionized water to form solution B;
[0051] Solution B was slowly added dropwise to solution A within 80 min, and then the mixture was refluxed at 100 °C for 72 h. The final product was filtered and washed with deionized water, 0.2 M ammonia water, and deionized water, respectively, to obtain a black product. The product was then placed in a vacuum drying oven at 60 °C for 24 h to obtain PDAP.
[0052] Figure 1 Figure 3 is the H NMR spectrum of PDAP. It can be seen that PDAP exhibits a very broad band in the chemical shift range of 6-9 ppm, which is consistent with the -NH2 / -NH- groups and aromatic rings of the polymer chain, indicating that the synthesized material is PDAP.
[0053] 2) Preparation of organic negative electrode:
[0054] 120 mg PDAP, 60 mg Ketjen black (KB), and 20 mg polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 6:3:1, and an appropriate amount of isopropanol was added. The mixture was ground in an agate mortar for 45 min, placed in a vacuum drying oven at 40 °C for 40 min, and then the material was kneaded into a plasticine-like state and pressed into thin sheets;
[0055] Use scissors to cut into 1*1cm2 A small piece of electrode material is pressed onto nickel foam at a pressure of 10 MPa to obtain an organic negative electrode.
[0056] Figure 2 This is the cyclic voltammetry curve of PDAP at 5mV / s in a three-electrode system. During the discharge process, two peaks corresponding to the reduction reaction appear: -0.77V and -0.92V. During the charging process, one peak corresponding to the oxidation reaction appears: -0.59V. This shows that the redox reaction of PDAP is carried out in steps, with high reversibility and low potential, making it suitable as a negative electrode.
[0057] 3) Preparation of modified electrolyte:
[0058] KOH was dissolved in deionized water to prepare a 6M KOH electrolyte, to which 1,4-dioxane and dimethyl sulfoxide were added so that the mass ratio of 1,4-dioxane, dimethyl sulfoxide, and KOH was 1:1:6 to obtain an electrolyte KOH. DIO .
[0059] 4) Aqueous battery assembly:
[0060] PDAP organic electrode was used as negative electrode and KOH DIO The electrolyte, PP / PE and 10 mm diameter sintered nickel were used as the positive electrode to assemble a CR2032 button battery.
[0061] Figure 3 This is a cycle stability test chart of the aqueous battery prepared in this embodiment after 120 cycles at 0.12 A / g. It can be seen that the first discharge capacity of PDAP at 0.12 A / g is 222.2 mAh / g, the discharge capacity of PDAP after 120 cycles is 203.3 mAh / g, and the capacity retention rate is 91.49%.
[0062] Comparative Example 1
[0063] The difference between this comparative example and Example 1 is that the PDAP in the organic negative electrode material is adjusted to DAP, and the electrolyte is not modified. Specifically:
[0064] 1) Preparation of organic negative electrode:
[0065] 120 mg DAP, 60 mg Ketjen black (KB), and 20 mg polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 6:3:1, and an appropriate amount of isopropanol was added. The mixture was ground in an agate mortar for 45 min, placed in a vacuum drying oven at 40 °C for 40 min, and then the material was kneaded into a plasticine-like state and pressed into thin sheets;
[0066] Use scissors to cut into 1*1cm 2A small piece of electrode material is pressed onto nickel foam at a pressure of 10 MPa to obtain an organic negative electrode.
[0067] 2) Preparation of electrolyte:
[0068] KOH was dissolved in deionized water to prepare a 6 M KOH electrolyte.
[0069] 3) Aqueous battery assembly:
[0070] The CR2032 button battery of this comparative example was assembled using a DAP organic electrode as a negative electrode, a KOH electrolyte as an electrolyte, a PP / PE as a separator, and a sintered nickel with a diameter of 10 mm as a positive electrode.
[0071] Figure 4 This is the cycle stability test of the aqueous battery in this comparative example at 0.12A / g for 60 cycles. At 0.12A / g, the first discharge capacity of DAP is 235mAh / g, the capacity decay is 217mAh / g in the first 10 times, and then the capacity gradually increases to 219mAh / g, which corresponds to the activation process of DAP in constant current charge and discharge. After 60 cycles, the discharge capacity of DAP is 193.8mAh / g, and the capacity retention rate is 82.47%.
[0072] Comparative Example 2
[0073] The difference between this comparative example and Example 1 is that the PDAP in the organic negative electrode material is adjusted to DAP, specifically:
[0074] 1) Preparation of organic negative electrode:
[0075] 120 mg DAP, 60 mg Ketjen black (KB), and 20 mg polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 6:3:1, and an appropriate amount of isopropanol was added. The mixture was ground in an agate mortar for 45 min, placed in a vacuum drying oven at 40 °C for 40 min, and then the material was kneaded into a plasticine-like state and pressed into thin sheets;
[0076] Use scissors to cut into 1*1cm 2 A small piece of electrode material is pressed onto nickel foam at a pressure of 10 MPa to obtain an organic negative electrode.
[0077] 2) Preparation of electrolyte:
[0078] KOH was dissolved in deionized water to prepare a 6M KOH electrolyte, to which 1,4-dioxane and dimethyl sulfoxide were added so that the mass ratio of 1,4-dioxane, dimethyl sulfoxide, and KOH was 1:1:6 to obtain an electrolyte KOH. DIO .
[0079] 3) Aqueous battery assembly:
[0080] The CR2032 button battery of this comparative example was assembled using a DAP organic electrode as a negative electrode, a KOH electrolyte as an electrolyte, a PP / PE as a separator, and a sintered nickel with a diameter of 10 mm as a positive electrode.
[0081] Figure 5 The graph is a cycle stability test of the aqueous battery of this comparative example at 0.12 A / g for 120 cycles. At 0.12 A / g, the initial discharge capacity of DAP is 234.22 mAh / g, and after 120 cycles, the discharge capacity of DAP is 190.3 mAh / g, with a capacity retention rate of 84.92%.
[0082] The performance of the batteries prepared in Example 1 and Comparative Examples 1 and 2 are compared and the results are shown in Table 1.
[0083] Table 1
[0084] First discharge capacity Discharge capacity after 60 / 120 cycles Capacity retention rate Example 1 222.2mAh / g 203.3mAh / g(120cycle) 91.49% Comparative Example 1 235mAh / g 193.8mAh / g(60cycle) 82.47% Comparative Example 2 234.22mAh / g 190.3mAh / g(120cycle) 84.92%
[0085] It can be seen that when only 1,4-epoxyhexacyclic ring is added to the KOH electrolyte, the cycle stability of DAP is improved, but the improvement is small, from 82.47% in the initial 60 cycles to 84.92% in 120 cycles, while the solution of Example 1 of the present invention can be improved from 82.47% in the initial 60 cycles to 91.49% in 120 cycles.
[0086] Example 2
[0087] The difference between this embodiment and embodiment 1 is that the mass ratios of 1,4-dioxane, dimethyl sulfoxide, and KOH are adjusted to 1:2:6 and 1:1:7, and the remaining steps and processes are referred to embodiment 1, to obtain aqueous batteries with different mass ratios of 1,4-dioxane, dimethyl sulfoxide, and KOH in this embodiment, and performance tests are carried out. The results are shown in Table 2.
[0088] Table 2
[0089] Proportion First discharge capacity Discharge capacity after 120 cycles Capacity retention rate 1:1:6 222.2mAh / g 203.3mAh / g 91.49% 1:2:6 200.3mAh / g 155.2mAh / g 77.50% 1:1:7 213.25mAh / g 170.99mAh / g 83.25%
[0090] It can be seen that adjusting the mass ratio of 1,4-dioxane, dimethyl sulfoxide and KOH has a significant effect on the performance of the aqueous battery. This is because in the present invention, 1,4-dioxane and dimethyl sulfoxide, as additives, together with KOH, constitute the main body of the electrolyte. When the mass ratio between them changes, the physical and chemical properties of the electrolyte, such as viscosity, ion conductivity, and wettability to electrode materials, will also change accordingly, and affect the solubility of the negative electrode material, thereby affecting the cycle stability of the battery.
[0091] Comparative Example 3
[0092] The difference between this comparative example and Example 1 is that the 1,4-dioxane in the electrolyte is adjusted to 1,3-dioxolane, and the remaining steps and processes are referred to Example 1 to obtain the aqueous battery of this comparative example.
[0093] Comparative Example 4
[0094] The difference between this comparative example and Example 1 is that the dimethyl sulfoxide in the electrolyte is adjusted to ethylene glycol, and the remaining steps and processes are all referred to Example 1 to obtain the aqueous battery of this comparative example.
[0095] Comparative Example 5
[0096] The difference between this comparative example and Example 1 is that 1,4-dioxane in the electrolyte is omitted, and the remaining steps and processes are all referred to Example 1 to obtain the aqueous battery of this comparative example.
[0097] The performance of the aqueous battery obtained by comparing Example 1 with Comparative Examples 3 to 5 is shown in Table 3.
[0098] Table 3
[0099] First discharge capacity Discharge capacity after 120 cycles Capacity retention rate Example 1 222.2mAh / g 203.3mAh / g 91.49% Comparative Example 3 205.23mAh / g 175.06mAh / g 85.30% Comparative Example 4 186.93mAh / g 146.92mAh / g 78.60% Comparative Example 5 193.46mAh / g 146.64mAh / g 75.80%
[0100] It can be seen that the performance of the battery obtained by adjusting the electrolyte composition of the present application also has significant differences. For example, after replacing 1,4-dioxane with 1,3-dioxolane, although both are cyclic ether solvents, the differences in their physical and chemical properties may cause the solubility of 1,3-dioxolane in the electrolyte, the wettability to the electrode material, and the stabilizing effect on the organic negative electrode material PDAP to be inferior to 1,4-dioxane, so the cycle performance is greatly reduced.
[0101] In summary, the present application modifies the KOH electrolyte by adding 1,4-dioxane and dimethyl sulfoxide. Under a specific ratio, the solubility of the organic material PDAP can be effectively reduced, which not only broadens the electrochemical window of the water electrolyte, but also has a higher cycle life.
[0102] The aqueous battery produced by the present invention has the advantages of long cycle life and high output voltage, and the raw materials are widely available and inexpensive. It can effectively solve the problems of low energy density and short cycle life of existing aqueous batteries, and help promote the application of aqueous batteries in the field of large-scale energy storage.
[0103] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. An aqueous battery based on azine derivative, characterized in that: include, (i) It is composed of a positive electrode, a negative electrode, a separator and an electrolyte; (ii) the negative electrode comprises an oxazine derivative having a structural formula as shown in formula (I); X is selected from NH2, OH, NH3 + CH3COO - One of; (iii) The electrolyte is a KOH electrolyte modified by adding 1,4-dioxane and dimethyl sulfoxide.
2. The aqueous battery based on azine derivatives according to claim 1, characterized in that: The material of the positive electrode includes one of a nickel-based compound, a Prussian blue analogue or a polyanion compound.
3. The aqueous battery based on azine derivatives according to claim 1, characterized in that: The material of the diaphragm includes one or more of polyethylene, polypropylene diaphragm and PBI diaphragm.
4. The aqueous battery based on azine derivatives according to claim 1, characterized in that: The negative electrode further comprises Ketjen black and polytetrafluoroethylene, wherein the mass ratio of the oxazine derivative to the Ketjen black and polytetrafluoroethylene is 3-6:6-3:
1.
5. The aqueous battery based on azine derivatives according to claim 1, characterized in that: The KOH electrolyte, wherein the mass ratio of 1,4-dioxane, dimethyl sulfoxide and KOH is 1:1:5-7.
6. The method for preparing an aqueous battery based on azine derivatives according to claim 1, characterized in that: include, The CR2032 button battery is assembled with a diaphragm and a positive electrode material, using a oxazine derivative as the active material of the negative electrode and a modified KOH electrolyte as the electrolyte.
7. The method for preparing an aqueous battery based on azine derivatives according to claim 6, characterized in that: The synthesis method of the oxazine derivatives having the structural formula shown in formula (I) comprises: o-phenylenediamine is dissolved in acetic acid to form solution A; Ammonium persulfate is dissolved in deionized water to form solution B; Solution B is slowly added dropwise to solution A, and the mixture is heated under reflux for reaction. After the reaction is completed, the product is post-treated to obtain an oxazine derivative.
8. The method for preparing an aqueous battery based on azine derivatives according to claim 7, characterized in that: The molar ratio of o-phenylenediamine to ammonium persulfate is 1:2-4.
9. The method for preparing an aqueous battery based on azine derivatives according to claim 7, characterized in that: The reaction temperature of the heating reflux is 90-110° C., and the reaction time is 70-74 hours.
10. The method for preparing an aqueous battery based on azine derivatives according to claim 6, characterized in that: The method for preparing the negative electrode comprises: A oxazine derivative having a structural formula as shown in formula (I), Ketjen black, and polytetrafluoroethylene are mixed and then isopropyl alcohol is added. After grinding, the obtained material is vacuum dried, and the obtained material is kneaded into a clay-like state and then pressed into a thin sheet, which is pressed onto nickel foam to obtain a negative electrode.